1998
DOI: 10.1103/physrevd.57.2974
|View full text |Cite
|
Sign up to set email alerts
|

CPviolating anomalous couplings at a500GeVe+

Abstract: We study the sensitivity of a 500 GeV e ϩ e Ϫ linear collider to CP violating anomalous couplings. We find that with 50 fb Ϫ1 , and taking only one non-zero coupling at a time, the process e ϩ e Ϫ →W ϩ W Ϫ can be used to place the 95% confidence level bounds ͉ ␥ ͉р0.1, ͉ Z ͉р0.1 and ͉g 4 Z ͉р0.1 from CP even observables. By studying certain distributions in the process e ϩ e Ϫ → ϩ Ϫ one of the bounds can be improved to ͉g 4 Z ͉ р0.06. This process also allows the construction of a CP odd observable which can b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Similarly, one can probe CP-violation in the W W Z vertex at linear colliders [16] via the process e + e − → Z * → W + W − → lνlν. Note that the natural channel for observing this effect operates when running well above the Z-boson pole.…”
Section: Additional Applicationsmentioning
confidence: 99%
“…Similarly, one can probe CP-violation in the W W Z vertex at linear colliders [16] via the process e + e − → Z * → W + W − → lνlν. Note that the natural channel for observing this effect operates when running well above the Z-boson pole.…”
Section: Additional Applicationsmentioning
confidence: 99%
“…A competitive indirect limit |κ γ | < 0.6 has been derived recently [11] from the b → sγ CLEO data [12], whereas indirect constraints based on neutron electric dipole moment (EDM) put a very strong limit |κ γ | < ∼ 2 × 10 −4 [7]. By investigating e + e − → W + W − at a future 500 GeV linear collider, it has been shown that the constraint |κ γ | ≤ 0.1 can be established [13]. Similar conclusion has been reached for the process pp → W γ at an upgraded Tevatron [14].…”
Section: Anomalous Couplingsmentioning
confidence: 99%
“…CP -violating triple gauge-boson couplings (TGC) W W γ and W W Z in the highenergy e + e − collisions are investigated in Refs. [1,2,3,4,5,6] by constructing observables sensitive to these couplings. However, one may obtain quite strict limits on the TGC parameters from the analysis of the total cross-sections only.…”
Section: Introductionmentioning
confidence: 99%